Pengaruh Gaya Kepemimpinan, Lingkungan Kerja dan Stres Kerja terhadap Kinerja Karyawan PT NT Cikarang - Sinta Sundari Heriyanti; Rahma Putri (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2021)
This study aims to determine the effect of leadership style, work environment, and work stress on employee performance at PT. NT Indonesia. This type of research uses quantitative research. The sample in this study amounted to 74 respondents. Methods of data collection using a questionnaire. Data analysis using the SPSS program. The analysis used includes the analysis of the coefficient of determination, F Test, and Multiple Linear Regression Test. The results showed that leadership style affected employee performance, work environment affected employee performance, job stress affected employee performance.